2016
DOI: 10.3758/s13414-016-1253-x
|View full text |Cite
|
Sign up to set email alerts
|

Two distinct patterns of interference in between-attribute Stroop matching tasks

Abstract: In between-attribute Stroop matching tasks, participants compare the meaning (or the color) of a Stroop stimulus with a probe color (or meaning) while attempting to ignore the Stroop stimulus's task-irrelevant attribute. Interference in this task has been explained by two competing theories: A semantic competition account and a response competition account. Recent results favor the response competition account, which assumes that interference is caused by a task-irrelevant comparison. However, the comparison o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
2
10
0
Order By: Relevance
“…trials differed from neutral and/or congruent ones, indicating that response inhibition was influenced by the distracting information of the primary task; a pattern of results that was supported in other studies (e.g., Chambers et al, 2007;Ridderinkhof et al, 1999). Portugal et al (2018) combined stop-signal with a version of the Stroop task that involved different sources of interference, the Stroopmatching task (see also Afonso et al, 2020;Dittrich & Stahl, 2017). Participants were instructed to compare the Stroop-word (while ignoring its color) with two lateralized colored bars and choose the bar that matched the Stroopword.…”
Section: Both Studies Found That Ssrts Of Incongruentsupporting
confidence: 69%
See 1 more Smart Citation
“…trials differed from neutral and/or congruent ones, indicating that response inhibition was influenced by the distracting information of the primary task; a pattern of results that was supported in other studies (e.g., Chambers et al, 2007;Ridderinkhof et al, 1999). Portugal et al (2018) combined stop-signal with a version of the Stroop task that involved different sources of interference, the Stroopmatching task (see also Afonso et al, 2020;Dittrich & Stahl, 2017). Participants were instructed to compare the Stroop-word (while ignoring its color) with two lateralized colored bars and choose the bar that matched the Stroopword.…”
Section: Both Studies Found That Ssrts Of Incongruentsupporting
confidence: 69%
“…The Stroop-matching data confirmed the existence of the congruency effect; participants were slower and committed more errors in incongruent than in congruent trials. This performance in incongruent trials reflects the difficulty in overcoming the conflict between target and distractor Stroop attributes, an interference that is well established in the literature for both classic and matching Stroop tasks (e.g., Caldas et al, 2012;Dittrich & Stahl, 2017;Green et al, 2016;Portugal et al, 2018;Stroop, 1935).…”
Section: Stroop Interference: the Congruency Effectmentioning
confidence: 76%
“…This study presents an exciting modus operandi to answer the issue at hand: what are the neural origins and dynamics of cognitive conflict? A large body of research studying various conflict tasks has characterized fast errors as resulting from early response capture of irrelevant information (Coleman et al, 2017;Dittrich and Stahl, 2017;Duprez et al, 2016;Ellinghaus and Miller, 2017;Houvenaghel et al, 2016;Hughes and Yeung, 2011;Salzer et al, 2014;Stins et al, 2007;Wylie et al, 2009). Using a multivariate analysis techniques capitalizing on trial-to-trial variability in neural signal, we demonstrate that traces of the conflict arise in sensory brain areas that code for relevant and irrelevant Within the framework of the dual-route model, we formulated concrete predictions in a theoretically principled way (de Hollander et al, 2016;Forstmann et al, 2016Forstmann et al, , 2011Turner et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, EMG data revealed that these competing activations at response level affect motor performance and increase the frequency of double hand activations in trials with SMRC (Caldas et al, 2012). However, despite confirming that response conflict plays an important role in the Stroop-matching task interference, this does not exclude the joint participation of other mechanisms in the Stroop effect scenario, which remains as focus of debate (Luo, 1999;David et al, 2011;Caldas et al, 2012;Sturz et al, 2013;Green et al, 2016;Dittrich & Stahl 2017).…”
Section: Introductionmentioning
confidence: 93%
“…In this protocol, a congruent or incongruent Stroop stimulus is presented with another stimulus (e.g., a colored bar) and participants had to compare the relevant attributes of both stimuli according to the instructions (e.g., compare the word of the Stroop stimulus with the colored bar). After the pioneer work by Treisman and Fearnley (1969), several studies have explored the Stroop-matching task using different approaches in an attempt to better understand the interferences underlying the Stroop effect (Luo, 1999;Goldfarb & Henik, 2006;Caldas et al, 2012 and2014;Machado-Pinheiro et al, 2010;David et al, 2011;Dittrich & Stahl, 2017). In the classical Stroop task, response latencies for incongruent stimuli are longer than those for congruent stimuli -the congruency effect.…”
Section: Introductionmentioning
confidence: 99%